The role of television in the implementation of Russian state national policy: typology, genre, formats - Ekaterina K. Reva; Sergei D. Kubrin (RUDN Journal of Studies in Literature and Journalism, 2020)
The article presents the results of the analysis of the implementation of the tasks of the Strategy of the State National Policy of the Russian Federation for the period up to 2025 by television. The study was conducted on the basis of television information and analytical products defined by the Action Plans for the implementation of the Strategys objectives. Television programs included in the Plans are considered from 2013 to the present, taking into account the continuity of the Strategy, as the main doctrinal document in the field of national policy. In studying the role of the media in the implementation of the Strategy, the approach proposed in the article was applied for the first time. The analysis sampled and systematized television programs on the objectives of the Strategy. As a result of the study, typological features of television channels, genre characteristics of television programs are presented, journalistic techniques of implementation of tasks are defined, which programs identified in the Plans are more or less in line with the tasks of the Strategy of State National Policy are revealed. The study concluded that most television products meet the objectives of the Strategy and implement them.